The distribution of four species of the genus Macrourus (Gadiformes: Macrouridae) from the Southern Ocean based on samples from the toothfish longline fishery - Gon, Ofer; Miya, Tshoanelo; Mcmillan, Peter; Leslie, Robin (Zootaxa, 2021)
The known distribution of Macrourus caml is extended to the Ob and Lena Banks area, and southwest of Heard and McDonald Islands. Macrourus holotrachys was recorded from Prince Edward Islands and the Ob and Lena Banks. Macrourus carinatus specimens examined were all from Prince Edward Islands, the type locality. Macrourus whitsoni specimens examined were all from the southeast Atlantic Ocean at about 69˚S, close to the Antarctic continent (off Maud Land), consistent with a previous study which reported the species from 64–77˚S. A revised identification key is provided.